2015
DOI: 10.1038/ncomms7233
|View full text |Cite
|
Sign up to set email alerts
|

Interactome analysis identifies a new paralogue of XRCC4 in non-homologous end joining DNA repair pathway

Abstract: Non-homologous end joining (NHEJ) is a major pathway to repair DNA double-strand breaks (DSBs), which can display different types of broken ends. However, it is unclear how NHEJ factors organize to repair diverse types of DNA breaks. Here, through systematic analysis of the human NHEJ factor interactome, we identify PAXX as a direct interactor of Ku. The crystal structure of PAXX is similar to those of XRCC4 and XLF. Importantly, PAXX-deficient cells are sensitive to DSB-causing agents. Moreover, epistasis ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
198
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(217 citation statements)
references
References 40 publications
16
198
3
Order By: Relevance
“…In some cases, XLF and PAXX may work together to stabilize DNA ends. In reactions containing Ku, XRCC4·Lig4, and XLF, PAXX promoted the ligation of a blunt end to a 3' overhang (65). Interestingly, a more recent biochemical study showed that if Artemis and Pol m are included, PAXX does not stimulate NHEJ for 3' overhangs, but it does for 5' overhangs (73), indicating that the role of PAXX may be to stabilize substrates that cannot generate microhomology by end processing or nucleotide addition.…”
Section: Xlf and Paxx Stimulate Ligation By The Xrcc4·lig4 Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, XLF and PAXX may work together to stabilize DNA ends. In reactions containing Ku, XRCC4·Lig4, and XLF, PAXX promoted the ligation of a blunt end to a 3' overhang (65). Interestingly, a more recent biochemical study showed that if Artemis and Pol m are included, PAXX does not stimulate NHEJ for 3' overhangs, but it does for 5' overhangs (73), indicating that the role of PAXX may be to stabilize substrates that cannot generate microhomology by end processing or nucleotide addition.…”
Section: Xlf and Paxx Stimulate Ligation By The Xrcc4·lig4 Complexmentioning
confidence: 99%
“…Like XLF, PAXX also forms homodimers, and its C-terminus has been found to associate with Ku (64,65) (Fig. 2D).…”
Section: Xlf and Paxx Stimulate Ligation By The Xrcc4·lig4 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…S3A in the supplemental material). In addition, two laboratories recently have described another XRCC4/XLF-like factor, PAXX (25,26). PAXX interacts with DNA-bound Ku and can be targeted to sites of DNA damage.…”
Section: Xlfmentioning
confidence: 99%
“…This factor directly interacts with Ku and promotes DNA ligation; however, the exact role of this protein in V(D)J recombination is not yet known. 10,11 The diversity of the antigen receptors created during V(D)J recombination has been estimated to be more than 10 12 . Part of the diversity arises from different combinations of the V, D, and J genes (2 3 10 ends are processed during V(D)J recombination.…”
Section: Introductionmentioning
confidence: 99%